Disinfection by-products exposure and intra-uterine growth restriction: Do genetic polymorphisms of CYP2E1or deletion of GSTM1 or GSTT1 modify the association?. (July 2016) - Levallois, Patrick; Giguère, Yves; Nguile-Makao, Molière; Rodriguez, Manuel; Campagna, Céline; Tardif, Robert; Bureau, Alexandre
Abstract: Background: Exposure to disinfection by-products (DBPs) during pregnancy was associated with reduced foetal growth. Genetic susceptibility might play a role, especially for genes encoding for the Cytochrome P450 (CYP2E1) and Glutathione S-Transferase (GST) enzymes, involved in metabolism and activation of DBPs. Few epidemiological studies evaluated these gene-environment interactions and their results were never replicated. Objective: This study aims to examine interactions between trihalomethanes (THM) or haloacetic acids (HAA) exposure and genetic polymorphisms on small for gestational age (SGA) neonates by investigating single nucleotide polymorphisms (SNPs) in CYP2E1 gene and GSTM1 and GSTT1 deletions in mothers-children pairs. Methods: A population-based case-control study of 1549 mothers and 1455 children was conducted on SGA and THM/HAA exposure. DNA was extracted from blood or saliva cells. Targeted SNPs and deletions were genotyped. Statistical interaction between SNPs/deletions and THMs or HAAs in utero exposure with regard to SGA occurrence was evaluated by unconditional logistic regression with control of potential confounders. Results: Previously reported positive modification of the effect of THM uterine exposure by mothers or newborns CYP2E1 rs3813867 C allele or GSTM1 deletion was not replicated. However interactions with CYP2E1 rs117618383 and rs2515641 were observed but were not statistically significant after correction for multiple testing. Conclusions: Previous positive interactions between THMs exposure and CYP2E1 and GSTM1 were not replicated but interactions with other CYP2E1 polymorphisms are reported. Highlights: Fetal growth restriction was associated with disinfection by-products intra-uterine exposure. Modification of the association for child carriers of C alleles of the CYP2E1 rs3813867 polymorphism was not replicated. Modification of the association for mothers with deletion of the GSTT1 was not replicated. No statistically significant gene-environment interaction was found after correction for multiple testing.